Association of IL1RL1 rs3771180 and TSLP rs1837253 variants with asthma in the Guangxi Zhuang population in China. Issue 6 (7th May 2019) - Sun, Yan; Wei, Xuan; Deng, Jingmin; Zhang, Jianquan; He, Zhiyi; Yang, Meiling; Liang, Siqiao; Chen, Zhangrong; Qin, Huajiao
Abstract: Objective: IL‐1 receptor‐like 1 (IL1RL1) and thymic stromal lymphopoietin (TSLP) play important roles in asthma in various ways. IL1RL1 rs3771180 and TSLP rs1837253 single nucleotide polymorphisms (SNPs) are associated with asthma in some European nationals but not in Zhuang people. Accordingly, this study aimed to determine the associations of IL1RL1 rs3771180 and TSLP rs1837253 with asthma in Zhuang people. Methods: We performed a case‐control study to observe the association between the two polymorphisms and asthma in a Guangxi Zhuang cohort consisting of 123 asthmatic patients and 100 healthy controls. These individuals were recruited from the Department of Respiration of the First Affiliated Hospital of Guangxi Medical University. Multiplex PCR assay was used to identify the genotype of rs3771180 and rs1837253. Data were analyzed with SPSS 22.0 and SHEsis. Results: rs1837253 showed significant differences between asthmatic and control groups in allele comparison (OR = 2.15; 95% CI = 1.27‐3.63; P  = 0.004), as well as in the homozygote (OR = 4.83; 95% CI = 1.47‐16.47; P  = 0.012), heterozygote (OR = 2.69; 95% CI = 1.20‐6.00; P  = 0.016), and dominant (OR = 3.01; 95% CI = 1.39‐6.52; P  = 0.005) genetic models. However, the genotype frequencies of rs3771180 did not obviously differ. Conclusion: rs1837253 is associated with asthma susceptibility and may increase the risk of asthma in Zhuang people in Guangxi.